An Overview Of Outpatient Service Quality At RSIA AisyiyahSamarinda In 2025 - Mudassir Yunus; Nur Rohmah; Rahmat Bahtiar; Ratno Adrianto (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Service quality is a crucial factor for patient satisfaction and loyalty in healthcare facilities. The Government of Indonesia, through the Minister of Health Decree (Kemenkes) RI Number 129/Menkes/SK/II/2008, has set Minimum Service Standards (SPM) for outpatient satisfaction at ≥90%. A study in 2024 showed a relationship between service quality and patient satisfaction at RSIA Aisyiyah Samarinda, and an internal survey report for the January-June 2024 periodindicated that outpatient patient satisfaction was still below the 90% threshold. Objective : This study aims to provide an overview of outpatient service quality at RSIA Aisyiyah Samarinda in 2025 Research Methods/ Implementation Methods : This was a descriptive quantitative study using accidental sampling technique, with data collected from 110 respondents (n=110). The service quality variable was measured using five dimensions (Tangibles, Reliability, Responsiveness, Assurance, Empathy) Results : The results showed that the overall average service quality at RSIA Aisyiyah Samarinda reached 90.6%, which falls into the “Very Good” category and meets the minimum standards set by the Ministry of Health (Kemenkes). The dimensions that exceeded the standard were Assurance (92.5%), Empathy (92.1%), and Reliability (91.0%). However, two dimensions remained below the 90% threshold, namely Responsiveness (89.3%) and Tangibles (88.0%). Conclusion/Lesson Learned : The overview of outpatient service quality at RSIA Aisyiyah Samarinda in 2025 was categorized as very good